THE EFFECT OF DOSTINEX ON THE BODY - Axmedov Shamshod Jamshidovich (Лучшие интеллектуальные исследования, 2024)
Abstract. The physiological mechanisms controlling reproduction are closely linked to energy balance. In the recent years, accumulating evidence suggests that prolactin regulates metabolic functions, besides regulating breast development and stimulating milk formation.